2022
DOI: 10.1162/jocn_a_01838
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Generation of Subjective Vividness and Confidence during Naturalistic Memory Retrieval in Angular Gyrus

Abstract: Our subjective experience of remembering guides and monitors the reconstruction of past and simulation of the future, which enables us to identify mistakes and adjust our behavior accordingly. However, it remains incompletely understood what underlies the process of subjective mnemonic experience. Here, we combined behavior, repetitive TMS, and functional neuroimaging to probe whether vividness and confidence are generated differently during retrieval. We found that preretrieval repetitive TMS targeting the le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 71 publications
2
16
0
Order By: Relevance
“…First, the variation of self-self mentalisation, i.e., metacognition, exhibited greater representational similarity to individual variation in hippocampal MMS or rs-FC relative to amygdala MMS or rs-FC, indicating a close association between the meta-cognition and hippocampus. This result dovetails with previous research which has confirmed that hippocampal function (Ye et al, 2019;Zou & Kwok, 2022) and structure (Allen et al, 2017;Alkan et al, 2020) are highly correlated with meta-cognition. Further, given the essential role meta-cognition plays in other mentalising components according to interactive mentalising theory (Wu et al, 2020b), our finding supports the motivation to decipher the importance of the hippocampus during dynamic social interaction.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…First, the variation of self-self mentalisation, i.e., metacognition, exhibited greater representational similarity to individual variation in hippocampal MMS or rs-FC relative to amygdala MMS or rs-FC, indicating a close association between the meta-cognition and hippocampus. This result dovetails with previous research which has confirmed that hippocampal function (Ye et al, 2019;Zou & Kwok, 2022) and structure (Allen et al, 2017;Alkan et al, 2020) are highly correlated with meta-cognition. Further, given the essential role meta-cognition plays in other mentalising components according to interactive mentalising theory (Wu et al, 2020b), our finding supports the motivation to decipher the importance of the hippocampus during dynamic social interaction.…”
Section: Discussionsupporting
confidence: 92%
“…This means we could not reveal the contribution of rs-FC between the amygdala or hippocampus and specific brain regions or networks in the trinity. Future studies might uncover this by examining the rs-FC between the amygdala or hippocampus and some brain regions of interest, e.g., the temporoparietal junction (Biervoye et al, 2016; Bitsch et al, 2019), precuneus (Ye et al, 2019), cerebellum (Metoki et al, 2022) and angular gyrus (Zou & Kwok, 2022), or even the brain networks, e.g., the default mode network (Yeshurun et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are however other TMS studies that did not identify a causal role for the left AG in memory and information retrieval. For instance, TMS over the left AG did not interfere with episodic retrieval (Koen et al, 2018), affect recollection (Wynn et al, 2018), and with assessment of memory confidence (Zou and Kwok, 2022). These three studies suggested alternative roles for the left AG in encoding processes in subjective mnemonic experience (Koen et al, 2018), in improving both familiarity and the subjectively perceived confidence in participants with low baseline memory recognition (Wynn et al, 2018), and in gauging the vividness of memory (Zou and Kwok, 2022).…”
Section: Section 2: Causal Role(s) Evidenced By Transcranial Brain St...mentioning
confidence: 89%
“…Therefore, although a general positivity bias may be apparent, memories for negative items or events may be more precise and phenomenologically more vivid. It should be noted that vividness and confidence of memory, although often used interchangeably in memory research, may represent partially distinct constructs and rely on unique underlying neural systems (Zou & Kwok, 2022). The only existing study to assess the effect of valence on metamemory demonstrated reduced metacognitive efficiency for negative items (Legrand et al, 2021).…”
Section: Discussionmentioning
confidence: 99%